2020
DOI: 10.1371/journal.pone.0227893
|View full text |Cite
|
Sign up to set email alerts
|

Reduced bone mineral density among HIV infected patients on anti-retroviral therapy in Blantyre, Malawi: Prevalence and associated factors

Abstract: Introduction Use of tenofovir based anti-retroviral therapy (ART) in HIV patients is associated with low bone mineral density (BMD). Low BMD predisposes people living with HIV (PLWHIV) to fractures thereby increasing morbidity and mortality. Since the introduction of tenofovir based ARV regimens in 2011, information on the prevalence of low BMD in PLWHIV and receiving ART is still scarce in Malawi. This study aimed to determine the prevalence and associated factors of low BMD among adults living with HIV and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 37 publications
3
21
0
1
Order By: Relevance
“…The pathological mechanism between HIV and/or ART and bone related abnormalities remain to be elucidated, but are probably due to HIV and ART affecting the interactions between osteoclasts and osteoblasts. Furthermore, the loss of bone mineral density is frequently observed in HIV-infected patients with ART (Duvivier et al, 2009;van Vonderen et al, 2009;Grant et al, 2016;Hoy et al, 2017;Chisati et al, 2020b). HIV-infected patients placed on protease inhibitor (PI) regimens demonstrate bone loss in the spine, while the nucleoside/nucleotide reverse transcriptase inhibitor (NRTI) regimen is associated with bone loss at the hip (Hoy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The pathological mechanism between HIV and/or ART and bone related abnormalities remain to be elucidated, but are probably due to HIV and ART affecting the interactions between osteoclasts and osteoblasts. Furthermore, the loss of bone mineral density is frequently observed in HIV-infected patients with ART (Duvivier et al, 2009;van Vonderen et al, 2009;Grant et al, 2016;Hoy et al, 2017;Chisati et al, 2020b). HIV-infected patients placed on protease inhibitor (PI) regimens demonstrate bone loss in the spine, while the nucleoside/nucleotide reverse transcriptase inhibitor (NRTI) regimen is associated with bone loss at the hip (Hoy et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The use of antiretroviral therapy (ART) to treat human immunodeficiency virus (HIV) leads to reduced bone mineral density (BMD) [1][2][3]. Low BMD categorised as osteopaenia and osteoporosis may increase the incidence of fractures among people living with HIV (PLWHIV) [4] which may escalate the risk for morbidity and increase mortality.…”
Section: Introductionmentioning
confidence: 99%
“…BMD was assessed by DXA, using a QDR Discovery Hologic DXA in the femoral neck and DXA in the lumbar spine by total body DXA. For each scan, BMD, Z-scores were recorded as previously reported [ 9 11 ]. DXA measurements were performed in the femur (femoral neck and/or total hip) and lumbar spine in each patient.…”
Section: Methodsmentioning
confidence: 99%
“…We suggest the use of tenofovir alafenamide (TAF) molecule instead of tenofovir to reduce the risk of bone toxicity [35,36]. A recent study enrolled young HIV positive with low BMD showed tenofovir as a key molecule in ARV therapy [11]. TAF is a hepatitis B virus (HBV) nucleotide reverse transcriptase inhibitor for the treatment of chronic HBV infection in adults with compensated liver disease and has been approved by the Food and Drug Administration (FDA) for the treatment of HIV-1 in November 2015.…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation